The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.3928/1081-597x-20060901-09
|View full text |Cite
|
Sign up to set email alerts
|

Binocular Visual Performance After LASIK

Abstract: PURPOSE:To analyze binocular visual function after LASIK.METHODS: Eye aberrometry and corneal topography was obtained for both eyes in 68 patients (136 eyes). To evaluate visual performance, monocular and binocular contrast sensitivity function and disturbance index for quantifying halos were measured. Tests were performed under mesopic conditions. RESULTS: Binocular summation and disturbance index diminished signifi cantly (PϽ.0001) after LASIK with increasing interocular differences in corneal and eye aberra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…Compared to our previous study [14] we did not measure binocular functions of LD and CS in the present study. This does not reflect the actual viewing conditions of the patients, but we aimed to maximize the potential changes to be observed and we know that they would be more likely detected under monocular conditions, as binocular summation will tend to improve the results of LD [14, 37] and CS [38]. We also aimed to explore the correlations with HOA specific to each eye, which forced us to do follow a monocular analysis in this part of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to our previous study [14] we did not measure binocular functions of LD and CS in the present study. This does not reflect the actual viewing conditions of the patients, but we aimed to maximize the potential changes to be observed and we know that they would be more likely detected under monocular conditions, as binocular summation will tend to improve the results of LD [14, 37] and CS [38]. We also aimed to explore the correlations with HOA specific to each eye, which forced us to do follow a monocular analysis in this part of the study.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the relatively low interocular difference in optical quality in the normal subjects with baseline correction did not affect binocular summation. However, in clinical cases of laser refractive surgery, large interocular asymmetries are observed post-op leading to reduced binocular summation and stereopsis [23,25]. In such cases, binocular higher order aberration correction to improve the optical quality and reduce the interocular difference in aberrations will substantially improve binocular visual performance.…”
Section: Discussionmentioning
confidence: 99%
“…This is evident from previous studies of binocular vision in the presence of interocular difference in optical quality, pertaining to anisometropia [18,19], addition of monocular defocus [20], interocular differences in higher order aberrations [21], corneal shape [22,23], contrast and spatial frequency [24]. Such interocular differences in optical aberrations occur routinely after clinical procedures such as laser refractive surgery [23,25]. In general, binocular summation has been observed to decrease with increasing interocular difference in optical quality [20,22].…”
Section: Introductionmentioning
confidence: 94%
“…Although it is known that the mesopic contrast sensitivity function (CSF) can deteriorate monocularly after surgery, this deterioration is even greater in the binocular case when large interocular differences arise in corneal and total eye aberrations. The average deterioration of the binocular CSF was found to be 28%, exceeding 40% in any cases (Jiménez et al. , 2006).…”
Section: Introductionmentioning
confidence: 85%
“…, 2006). Recently, some authors have shown (Jiménez et al. , 2005, 2006) that the interocular differences in corneal and total aberrations and corneal asphericity correlate with a greater deterioration of binocular vision after refractive surgery under mesopic conditions.…”
Section: Introductionmentioning
confidence: 99%